Use of Portfolio Assessment in Teaching of Science - Bhaduri, Indrani S.; Bhaduri, Sreyoshi (SCHOOL SCIENCE, 2014)
Assessment is imperative in the teaching-learning process. The effect and efficiency of an educational endeavour rests on appropriate assessment. An effective assessment looks into whether or not the objectives of the learning process have been fulfilled. Assessment of the teaching-learning process is thus, in essence, a key into understanding not only the students’ potential and gauge the increment in the knowledge base, but can also be used to identify the factors which may enhance learning in a classroom environment. This paper looks at portfolio assessment in the context of a science classroom.